Transaction Costs in Housing Markets - Jos van Ommeren (Tinbergen Institute, 2008)
According to economic theory, there are no strong reasons to tax (or to subsidise) residential moves, although low levels of taxation may be potentially justified to deal with the presence of externalities and economic stability. This is in contrast to practise in most countries where governments have created strong barriers to moving (transaction taxes, rent control) which induces substantial transaction costs. Likely, the welfare losses due to these government-induced transaction costs are substantial.
Keywords: R21; R23; 330; Housing market; residential mobility; transaction costs; transaction taxes; rent control; Wohnungswechsel; Transaktionskosten; Soziale Wohnungspolitik; Bibliometrie; Welt